Influence of self-efficacy and social support on entrepreneurial behavior among Universiti Putra Malaysia undergraduate Students - Owunna, Royal; Alias, Siti Noormi; Ajobi, Alice Omoefe (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the influence of self-efficacy and social support on entrepreneurial behavior among Universiti Putra Malaysia undergraduate students. This study applied quantitative research, and correlational research design, the study samples comprised 100 graduate students at Universiti Putra Malaysia, Serdang employed a purposive sampling technique. Data was collected using online Google Forms and analyzed using SPSS version 29.0 for Windows. Findings revealed that self-efficacy and entrepreneurial behavior have a positive relationship, the findings of the study confirmed the argument proposed by the theory of self-efficacy Theory. Future recommendations were also provided in this study, the present study has provided evidence that entrepreneurial self-efficacy is an important constituent of entrepreneurial success which ultimately boosts the economy of a nation, this study is considerable for the universities in employing those study programs that help motivate students to start their businesses and such workshops should be made part of the curriculum to achieve their entrepreneurial goals and reach the expected success in entrepreneurship.